2006
DOI: 10.1016/j.ejheart.2005.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Measuring body composition in chronic heart failure: A comparison of methods

Abstract: Aims: Fat-free mass (FFM) is increasingly recognized as a systemic marker of disease severity in chronic organ failure and is an important target for physiologic and pharmacologic interventions to improve functional status. The aim of this study was therefore to evaluate two clinical methods to assess FFM in patients with chronic heart failure (CHF) using deuterium dilution (DEU) as reference and bromide dilution to assess the ratio between intracellular (ICW) and extracellular water (ECW) as potential confoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 36 publications
2
29
0
1
Order By: Relevance
“…Hypertension is a major risk factor for adverse cardiovascular events and is endemic in end-stage renal disease patients [36]. Although the pathophysiology of hypertension in dialysis patients is multifactorial, many studies in recent years have suggested that volume overload may be the most important etiology [37,38,39,40]. In one study by Gunal et al [41], hypertension was completely normalized through strict fluid volume control.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is a major risk factor for adverse cardiovascular events and is endemic in end-stage renal disease patients [36]. Although the pathophysiology of hypertension in dialysis patients is multifactorial, many studies in recent years have suggested that volume overload may be the most important etiology [37,38,39,40]. In one study by Gunal et al [41], hypertension was completely normalized through strict fluid volume control.…”
Section: Discussionmentioning
confidence: 99%
“…However, charted daily fluid balance do seem to be a more useful guide in determining the risk of fluid overload than daily weights in the ICU, which can be inaccurate in guiding fluid management in the critical care setting. 108 Bioelectrical impedance bodycomposition analysis (BIA), a noninvasive method of fluid assessment, can provide estimates of total-body, extracellular, and intracellular water to allow the quantification of fluid overload and setting of dry weight 109,110 ; BIA is used widely in determining the fluid status in patients with end-stage renal failure on hemodialysis or peritoneal dialysis. However, this technology has not been extensively validated in critical care; its benefit over use of a well-kept fluid balance has not yet been established.…”
Section: Fluid Removal: Diuretics Ultrafiltration and Monitoringmentioning
confidence: 99%
“…However charted daily fluid balance does appear to be a more useful guide in determining risk of fluid overload than daily weight, which can be inaccurate in the critical care setting [69]. However even the most accurate fluid balance will fail to account for uncertain fluid status at ICU admission.…”
Section: De-resuscitation Strategiesmentioning
confidence: 99%